If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying s + -4 = 91 Reorder the terms: -4 + s = 91 Solving -4 + s = 91 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + s = 91 + 4 Combine like terms: -4 + 4 = 0 0 + s = 91 + 4 s = 91 + 4 Combine like terms: 91 + 4 = 95 s = 95 Simplifying s = 95
| 63-6x=3x+19 | | -7(3c-8)+4(9+11c)= | | 3+x=5-4(2) | | 14x+8=5(x-3)+5 | | 6-9x=-12x-6 | | -7(1-4m)=13(2m-4) | | 9x-6+56-32x=12+6(x) | | 1.25x+x=9 | | 69+2d=84+3d | | 7x+7x=112 | | 5a+4(3a-8)= | | 4a-4=-2a+15 | | 4.72f-0.5-61.6f=-8.3f | | 0.456=-0.3 | | 1.25+x=9 | | 6a+11=4a+37 | | 15=7+8(3b-8) | | 3y-2(2y-7)=(3+y)-4 | | 2x-7=3-x | | 2(x-2)=3x-(x+3) | | 13x-3x=-28+8x | | 7h=35 | | 9y+18=27 | | 27x=7+6x | | 4.72f-0.5=-61.6f-8.3f | | 0.25x-3=7(x+3)-0.5x | | 11n-6+n=2n-26 | | 8=3+6y | | 8(3b-8)+7=15 | | 11p-4=6p-1 | | 80=23-3 | | 6d=11 |